Vulnerability Assessment and Mitigation Strategies Against Mozi Botnet Attacks in IoT Environments - Walhidayat Walhidayat; Ahmad Zamsuri; Yuhelmi Yuhelmi; Muhamad Sadar (Universitas Dharma Wacana, 2026)
The rapid proliferation of Internet of Things (IoT) devices has introduced significant security gaps, making them prime targets for large-scale botnet infiltrations. Among these threats, the Mozi botnet has emerged as a formidable challenge due to its decentralized peer-to-peer (P2P) structure and its ability to exploit weak credentials and unpatched vulnerabilities. This study conducts a comprehensive vulnerability assessment and proposes strategic mitigation frameworks to counter Mozi botnet attacks. Using a laboratory-controlled environment, we simulated Mozi’s propagation vectors, specifically focusing on its exploitation of Telnet brute-forcing and command injection vulnerabilities. The assessment identifies critical weaknesses in IoT firmware and network configurations that facilitate rapid infection. Furthermore, this research evaluates several mitigation strategies, including implementing customized Intrusion Detection System (IDS) rules, network micro-segmentation, and automated patch management. The results demonstrate that a multi-layered defense approach can reduce the probability of successful infiltration by up to [insert percentage, e.g., 85%]. This study provides actionable insights for network administrators and IoT manufacturers to enhance the resilience of IoT ecosystems against evolving P2P-based threats.